(untitled) (Journal of Environmental Science and Natural Resources, 2025)
A study was attempted in Sadar Upazila of Jessore District, Bangladesh during February, 2019 to analyze value chain of vegetables, identifying value chain actors and women participation in this value chain focusing two promising vegetables namely brinjal and pointed gourd. Data were collected from both primary and secondary sources. The primary data were collected through face-to-face interview of 5 Loop aggregates, 45 farmers, 10 wholesalers, 15 retailers and 15 consumers using a pre-tested structured questionnaire and analyzed using STATA software. The value chain analysis was undertaken in qualitative terms. Socio-demographic and economic variables were analyzed by using descriptive statistics. The level of male and female farmers in these activities has been calculated by three different score (Participation index = regularly involved x 2, occasionally involved x 1 and never involved x 0) given on the basis of extent of participation. To analyze the access of males and females to and control over resources and benefits of vegetables, Chi-square test was applied for measuring the degree of association among variables. Vegetables value chain actors identified in the study that include input suppliers, producers, LOOP aggregators, retailers, wholesalers, aratders and consumers. The study identified that value chain was fully dominated by male but at the lower level, women involvement was also considerable. They have mainly participated in activities such as, harvesting, sorting, cleaning and storing of vegetables. Policy aiming at increasing farmers’ access to modern inputs, more women participation, improving extension activities and the coverage of LOOP system are recommended in the existing value chain to accelerate the chain’s development. Environ. Sci. & Natural Resources, 14(1&2): 41-44, 2025